2020
DOI: 10.2174/1573399815666191104115449
|View full text |Cite
|
Sign up to set email alerts
|

Improved Clinical Outcomes with Dulaglutide as Add-on Medication to Oral Antidiabetic Drugs with or Without Insulin in Overweight Indian Patients with Type 2 Diabetes Mellitus: Retrospective Study in a Real-World Setting

Abstract: Aim: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have demonstrated several extra-pancreatic benefits in addition to glycemic control. This study retrospectively evaluates the realworld clinical effectiveness of dulaglutide as add-on therapy in overweight patients with inadequately controlled type 2 diabetes mellitus (T2DM). Materials and Methods: This single-center study included overweight adult patients (N, 85; women, 45) with inadequately controlled T2DM (mean glycated hemoglobin [HbA1c] (standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Several recent real-world studies have shown consistent glucose-lowering efficacy with body weight reduction in patients with T2DM treated with dulaglutide when compared with the results from previous RCTs. 9 10 Similar findings from Korean patients with T2DM were reported in two studies that evaluated the glycemic efficacy of dulaglutide for 6 months. 11 12 However, little is known about the differences in glucoselowering efficacy of dulaglutide according to the background glucose-lowering regimen.…”
Section: Introductionsupporting
confidence: 70%
“…Several recent real-world studies have shown consistent glucose-lowering efficacy with body weight reduction in patients with T2DM treated with dulaglutide when compared with the results from previous RCTs. 9 10 Similar findings from Korean patients with T2DM were reported in two studies that evaluated the glycemic efficacy of dulaglutide for 6 months. 11 12 However, little is known about the differences in glucoselowering efficacy of dulaglutide according to the background glucose-lowering regimen.…”
Section: Introductionsupporting
confidence: 70%
“…The initiation of dulaglutide therapy can be considered in various clinical settings; however, given the concerns associated with insurance coverage, dulaglutide is generally used in combination therapy with OAD or basal insulin. Several recent real-world studies have shown consistent glucose-lowering e cacy with body weight reduction in patients with T2DM treated with dulaglutide when compared with the results from previous RCTs [9,10]. Similar ndings from Korean patients with T2DM were reported in two studies that evaluated the glycemic e cacy of dulaglutide for 6 months [11,12].…”
Section: Introductionsupporting
confidence: 65%
“…On the other hand, the administration of dulaglutide for 12 wk at a dose of 0.75 mg once weekly in patients with NAFLD reduced HbA 1c levels, body weight, transaminases and liver stiffness[ 42 ]. In another study in 85 overweight patients with inadequately controlled T2DM conducted in India, treatment with dulaglutide 1.5 mg once weekly for 20 wk resulted in significant reductions in HbA 1c , body weight, ALT and AST levels[ 43 ]. Also, in a post hoc analysis of four randomized, placebo-controlled trials in patients with T2DM ( n = 1499), dulaglutide decreased transaminase and γGT levels compared with placebo, particularly in patients with elevated transaminase levels at baseline[ 44 ].…”
Section: Lixisenatide and Dulaglutidementioning
confidence: 99%